Электронные технологии в методическом обеспечении учебного процесса - Тусаева, А.К.; Масакова, С.С. (My University, 2016)
Relevance. The article describes the main aspects of the creation of electronic textbooks, basic requirements and additional audio-video program for electronic textbooks. Goal. Identify and disclose the main factors creating and training on electronic technology. Method. In this article there were used comparative and descriptive methods. Results. The development of electronic technology in the educational process makes learning more free, but at the same time more complex. Conclusions. Create the responsible business unit that will organize projects for electronic books is also necessary to encourage teachers authors of electronic textbooks in the form of financial incentives or by making hours of teacher workload.
Keywords: Innovation; electronic technologies; electronic textbooks; educational process; tutor